التدابير العقابية لمكافحة السرقة العلمية على ضوء القرار الوزاري 1082 - العمري حكيم; مناد إشراق (University Of Eloued جامعة الوادي, 2023)
This study deals with one of the phenomena that has eroded the body of academic research at all levels, which is the phenomenon of scientific or literary plagiarism, or what is known as plagiarism and breach of scientific honesty. Related to the prevention of scientific plagiarism and methods of combating it, where we try to present and analyze the aspects of the phenomenon covered by the resolution and identify its forms and methods of combating it.
Punitive measures to combat scientific theft in the light of Ministerial Resolution 1082
مداخلة
Keywords: السرقة العلمية; القرار 1082; التدابير العقابية; scientific theft; resolution 1082; punitive measures